SCEL-based science learning to strengthen problem-solving skills and eco-religious attitudes in supporting the SDGs - Virginia, Lintang; Jauhariyah, Mukhayyarotin Niswati Rodliyatul; Yuberti, Yuberti; Abdullah, Isa; Ardani, Miftakhul Aulia; Sofita, Mita (Universitas Islam Negeri Raden Intan Lampung, 2026)
Climate change, environmental degradation, and sustainability challenges require science education to foster students' problem-solving skills and environmental responsibility. However, few studies have integrated scientific creativity, structured problem-solving, and eco-religious values within a single framework. This study investigated the effectiveness of the Scientific Creativity Eco-Religious Learning (SCEL) model in enhancing students' problem-solving skills and fostering eco-religious attitudes. A quasi-experimental design with a non-equivalent control group involved 120 tenth-grade students. Data were collected through tests, questionnaires, observations, and open-ended responses and analyzed using nonparametric statistics. The findings showed that students taught using the SCEL model achieved higher problem-solving gains than those receiving project-based learning instruction, with a significant difference (p < 0.05) and a large effect size (r = 0.53). Students also demonstrated stronger eco-religious attitudes. These results suggest that integrating scientific creativity, structured problem-solving, and eco-religious reflection can promote holistic learning by balancing cognitive competencies with environmental responsibility. These findings indicate that SCEL provides an integrated framework for sustainability-oriented science learning by combining scientific creativity, structured problem-solving, and eco-religious values, thereby supporting SDG 4 (Quality Education) and SDG 13 (Climate Action).